Do the gods wear capes? : spirituality, fantasy, and superheroes - Saunders, Ben, 1968- (New York : Bloomsbury, 2013)
"Brash, bold, and sometimes brutal, superheroes might seem to epitomize modern pop-culture at its most melodramatic and mindless. But according to Ben Saunders, the appeal of the superhero is fundamentally metaphysical - even spiritual - in nature. In chapter-length analyses of the early comic book adventures of Superman, Wonder Woman, Spider-Man, and Iron-Man, Saunders explores a number of complex philosophical and theological issues, including: the problem of evil; the will-to-power; the tension between intimacy and vulnerability; and the challenge of love, in the face of mortality"--Page [4] of cover.
Introduction : The power of love -- Superman : truth, justice, and all that stuff -- Wonder Woman : bondage and liberation -- Spider-Man : heroic failure and spiritual triumph -- Iron Man : techno-faith -- Coda : modern gods -- Appendix : On the place of superhero studies within comics studies.
Includes bibliographical references (pages 152-174) and index.
"First published in 2011 by the Continuum International Publishing Group Ltd. Reprinted by Bloomsbury Academic 2013"--Title page verso.
Keywords: Superheroes -- Religious aspects; Heroes -- Comic books, strips, etc. -- History and criticism; Superheroes -- Moral and ethical aspects